2017
DOI: 10.1080/21691401.2017.1414823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-terminal and C-terminal modification on cytotoxicity and cellular uptake of amphiphilic cell penetrating peptides

Abstract: In conclusion, it was shown that cytotoxicity of modified peptides which were physically linked with MTX, considerably higher than both physically loaded unmodified peptides and chemically conjugated peptides with MTX. Also, cell internalization was reduced after peptide end-protection. These findings confirmed the effectiveness of N- and C-terminal modifications on cell viability and CPPs internalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…This means that the CNN model found a higher correlation between the terminal regions of the ACPs and observed activities. This observation is in agreement to our current understanding about the functionality of ACPs. , First, for peptides that target cell membranes, the terminal region with certain structure (such as structural amphiphilicity) or certain physicochemical properties (especially polar, charged, or hydrophobic residues) can help to achieve a higher affinity with the membrane, thereby helping them to penetrate the target cell. ,, Second, there are hundreds of proteases or peptidases that cause proteolysis of peptides; previous studies revealed that sequences terminated with residues such as M, S, A, T, V and G are more resistant to plasma degradation, thus certain compositions in the terminal regions of peptides can help them to improve in vivo stability and maintain bioactivity. In addition, studies that artificially modified ACPs for improved activity often mutated residues in the two terminals, ,,, which also reflects the functional importance of the terminal regions. Therefore, the contribution factor analysis shows that the breast model successfully learned some sequential patterns of the breast cancer ACPs and was able to relate these patterns to their functional activity.…”
Section: Resultssupporting
confidence: 87%
“…This means that the CNN model found a higher correlation between the terminal regions of the ACPs and observed activities. This observation is in agreement to our current understanding about the functionality of ACPs. , First, for peptides that target cell membranes, the terminal region with certain structure (such as structural amphiphilicity) or certain physicochemical properties (especially polar, charged, or hydrophobic residues) can help to achieve a higher affinity with the membrane, thereby helping them to penetrate the target cell. ,, Second, there are hundreds of proteases or peptidases that cause proteolysis of peptides; previous studies revealed that sequences terminated with residues such as M, S, A, T, V and G are more resistant to plasma degradation, thus certain compositions in the terminal regions of peptides can help them to improve in vivo stability and maintain bioactivity. In addition, studies that artificially modified ACPs for improved activity often mutated residues in the two terminals, ,,, which also reflects the functional importance of the terminal regions. Therefore, the contribution factor analysis shows that the breast model successfully learned some sequential patterns of the breast cancer ACPs and was able to relate these patterns to their functional activity.…”
Section: Resultssupporting
confidence: 87%
“…In addition to many bioactive peptides, the C-terminus of the heavy chain of many monoclonal antibody-based drugs is amidated, although its significance is not yet known (Tsubaki et al 2013). Since cells contain exopeptidases, the C-terminus of the cellpenetrating peptides is often amidated, which increases their half-life (Soleymani-Goloujeh et al 2017).…”
Section: C-termini Backgroundmentioning
confidence: 99%
“…The release exponent “ n ” was 0.185, which agreed with the porous nature of MSN, with a release diffusion behavior that is quasi-Fickian in characteristics (Figure D­(III)). The sustained release behavior may be attributed to hydrogen bonding and electrostatic interaction between the functional groups existing in TAT and the carboxylic group of the MTX. , In addition, release of the drug inside the channel of MSNs can be hindered by TAT acting as caps. Because the cap can be removed in acidic conditions, the release became faster (Figure D­(I),D­(II)).…”
Section: Results and Discussionmentioning
confidence: 99%